ANALISIS HUKUM ATAS PEMERIKSAAN KEKAYAAN NEGARA PADA BADAN USAHA MILIK NEGARA (BUMN) MENGENAI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 48 DAN 62/PUU-XI/2013 - Selatieli Zendrato; Bismar Nasution; Sunarmi Sunarmi; Faisal Akbar Nasution (Universitas Sumatera Utara, 2016)
ABSTRACT There is the difference in interpreting separated State’s assets. Many legal practitioners point out that separated State’s assets are corporations’ assets, but some of them point out that the assets of BUMN (State’s Owned Enterprises) are State’s assets because they come from State’s finance so that the Supreme Audit Agency has the authority to audit the assets of BUMN although. Concerning the assets of BUMN as an independent a corporation, and the status of the State as the capital owner, its position is only as a shareholder. According to the theory of legal entity, Public Accountant has the authority to audit the assets of BUMN as a corporation. The Institutional Court’s Ruling No. 48/PUU-XI/2013 does not pay attention to the position of BUMN whether it a public law or a private law. When a company has signed its memorandum of association before a Notary, private law is automatically in effect. The Constitutional Court in its Ruling No. 62/PUU-XI/2013 does not consider legal experts’ opinion which states that when BUMN uses money in the company, it does not use the provision on APBN (the National Budget) system which is regulated by the government but is only based on business judgment rule. Keywords: Auditing State’s Assets, BUMN, Constitutional Court’s Ruling.